STORY, STYLE AND INTERNAL TYPES IN THE STORY GENRE (Journal of Science-Innovative Research in Uzbekistan, 2024)
The current renewal period and human spirituality require a deeper approach to some issues of artistic creation, a new understanding of today's process and a number of theoretical ideas. The relationship of style, art and genre plays a significant role in this series of issues. Indeed, “in relation to the concept of style, various problems have arisen, such as style and method, style and form, style and genre relations, as well as methodological directions and style comparisons (typology). requires input